2020
DOI: 10.3390/biom10030384
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative-Antioxidant Imbalance and Impaired Glucose Metabolism in Schizophrenia

Abstract: Schizophrenia is a neurodevelopmental disorder featuring chronic, complex neuropsychiatric features. The etiology and pathogenesis of schizophrenia are not fully understood. Oxidative-antioxidant imbalance is a potential determinant of schizophrenia. Oxidative, nitrosative, or sulfuric damage to enzymes of glycolysis and tricarboxylic acid cycle, as well as calcium transport and ATP biosynthesis might cause impaired bioenergetics function in the brain. This could explain the initial symptoms, such as the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 268 publications
(379 reference statements)
1
20
0
Order By: Relevance
“…The expression of antioxidative genes, i.e., SOD2, PKD1, and NAPG (classic neuroleptics), or BDH1, ACAMD, and NAGS (atypical neuroleptics), as well as the level of proinflammatory cytokines, is also reduced [ 111 ]. Campo et al showed that the use of olanzapine causes a reduction in Acetyl-CoA levels in the mitochondrial cytosol and a weakening of insulin signaling by reducing the phosphorylation of Akt and reducing the expression of Opa-1 protein via the Akt-mTOR-NFκB-Opa-1 signaling pathway [ 109 , 112 ] as we wrote in our previous work [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of antioxidative genes, i.e., SOD2, PKD1, and NAPG (classic neuroleptics), or BDH1, ACAMD, and NAGS (atypical neuroleptics), as well as the level of proinflammatory cytokines, is also reduced [ 111 ]. Campo et al showed that the use of olanzapine causes a reduction in Acetyl-CoA levels in the mitochondrial cytosol and a weakening of insulin signaling by reducing the phosphorylation of Akt and reducing the expression of Opa-1 protein via the Akt-mTOR-NFκB-Opa-1 signaling pathway [ 109 , 112 ] as we wrote in our previous work [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic oxidative, nitrosative, or sulfuric stress resulting from oxidant–antioxidant imbalance may be one of the causes of mitochondrial dysfunction and may consistently oxidize lipids, proteins, and DNA impairing their basic biological functions [ 50 ]. MDA formed in the reaction is one of the important markers of oxidative stress and the final product of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with other RNS, this contributes the damage of cell membranes, proteins, and lipid membrane leading to the degradation of mitochondria, lysosomes, and DNA. The chain of events culminates in the inhibition of immune response and production of carcinogenic nitrosamines [ 125 ]. Nitric oxide (NO) is also involved in metal homeostasis including Fe, Cu, and Zn [ 126 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The paper by Bryll et al [ 6 ] extensively reviewed the currently reported role and mutual interactions of oxidative damage and impaired glucose metabolism as key factors affecting metabolic complications in schizophrenia. These observations may be a premise for novel potential therapeutic targets that will delay not only the onset of first symptoms but also the progression of schizophrenia and its complications.…”
mentioning
confidence: 99%